2016
DOI: 10.1080/00343404.2016.1175554
|View full text |Cite
|
Sign up to set email alerts
|

Firm performance in the periphery: on the relation between firm-internal knowledge and local knowledge spillovers

Abstract: This paper challenges one of the fundamental propositions within economic geography; that location in knowledge regions contributes to firm performance in general and especially for knowledge intensive firms that compete on the basis of knowledge. Our analysis of Swedish micro-data on 32,535 firms from 2004-2011 provides evidence that knowledge intensive firms benefit less from local knowledge spillovers than firms with comparably low in-house knowledge. This suggests that firms with high internal competencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 62 publications
5
39
0
1
Order By: Relevance
“…Most of the investigated firms value the protective environment of peripheral regions, especially concerning labour poaching. Our results thus confirm findings from other recent studies (Grillitsch & Nilsson, ). Many respondents point to a high loyalty of the workforce (especially in R&D departments) and highlight its advantages: It limits undesirable knowledge spill‐overs, protects tacit knowledge, and strengthens the internal knowledge base (Flåten et al, ; Isaksen, ).…”
Section: Results: Compensation and Exploitation Strategies Of Innovatsupporting
confidence: 94%
See 2 more Smart Citations
“…Most of the investigated firms value the protective environment of peripheral regions, especially concerning labour poaching. Our results thus confirm findings from other recent studies (Grillitsch & Nilsson, ). Many respondents point to a high loyalty of the workforce (especially in R&D departments) and highlight its advantages: It limits undesirable knowledge spill‐overs, protects tacit knowledge, and strengthens the internal knowledge base (Flåten et al, ; Isaksen, ).…”
Section: Results: Compensation and Exploitation Strategies Of Innovatsupporting
confidence: 94%
“…The findings also have implications for mainstream economic geography. In line with recent research (Fitjar & Rodríguez‐Pose, ; Grillitsch & Nilsson, , ; Isaksen, ; Meili & Shearmur, ; Shearmur & Doloreux, ), this paper has shown that innovation studies must overcome their predominant focus on core regions to also include conceptual and empirical work on innovation in peripheral regions. Furthermore, these findings contribute to the policy debate, as they dismiss the dominant unfavourable view on peripheral locations.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…(Firm 6,Interviewee 26) This result corroborates the finding of Grillitsch and Nilsson (2017) that knowledge-intensive firms might suffer from (negative) knowledge spillovers which are more likely to happen in urbanized regions. But there are committees where we have exchanges [with firms in the same industry], for example, the Iron Link Network.…”
Section: Dimension 3: External Knowledge Sourcessupporting
confidence: 78%
“…Our observations contribute to understanding why Grillitsch and Nilsson (2017) find no evidence that knowledge-intensive firms grow faster in knowledge-rich regions, and shed light on the question of how firms in small towns are able to maintain up-to-date and relevant knowledge. Our observations contribute to understanding why Grillitsch and Nilsson (2017) find no evidence that knowledge-intensive firms grow faster in knowledge-rich regions, and shed light on the question of how firms in small towns are able to maintain up-to-date and relevant knowledge.…”
Section: Discussionmentioning
confidence: 70%